2022
DOI: 10.1038/s41467-022-33037-x
|View full text |Cite
|
Sign up to set email alerts
|

An EGFR/HER2-targeted conjugate sensitizes gemcitabine-sensitive and resistant pancreatic cancer through different SMAD4-mediated mechanisms

Abstract: Chemoresistance limits its clinical implementation for pancreatic ductal adenocarcinoma (PDAC). We previously generated an EGFR/HER2 targeted conjugate, dual-targeting ligand-based lidamycin (DTLL), which shows a highly potent antitumor effect. To overcome chemoresistance in PDAC, we aim to study DTLL efficacy when combined with gemcitabine and explore its mechanisms of action. DTLL in combination with gemcitabine show a superior inhibitory effect on the growth of gemcitabine-resistant/sensitive tumors. DTLL s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Additionally, research has shown that loss of SMAD4 function can contribute to reduced sensitivity to EGFR/ERBB2-targeted drugs. [31][32][33] Unfortunately, because of the limited availability of effective therapeutics against KRAS and SMAD4 mutations, we were unable to control the disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research has shown that loss of SMAD4 function can contribute to reduced sensitivity to EGFR/ERBB2-targeted drugs. [31][32][33] Unfortunately, because of the limited availability of effective therapeutics against KRAS and SMAD4 mutations, we were unable to control the disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al developed an EGFR/HER2-targeting conjugate, the dual-target ligand-based lidamycin (DTLL), which prevents tumour proliferation in SMAD4/DPC4-deficient PDAC through ATK/mTOR blockade and impaired NF-κB function, and also restores SMAD4/DPC4 bioactivity, triggering downstream NF-κB regulation in SMAD4/DPC4-deficient tumours of signalling to overcome chemoresistance. In combination with gemcitabine, DTLL exhibits a unique mechanism of action similar to that of SMAD4/DPC4, showing superior inhibition of the growth of gemcitabine-resistant/sensitive tumours [86]. Fei et al found that the addition of hydroxychloroquine to neoadjuvant chemotherapy in patients with PDA may improve the therapeutic response in SMAD4/DPC4-deficient patients.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…The ve-year survival rate for pancreatic cancer is below 5%. 1,2 The majority of patients are diagnosed with advanced-stage disease that cannot be treated surgically, resulting in a life expectancy of typically less than six months. 3,4 Pancreatic cancer is a multifactorial disease that arises from a combination of factors.…”
Section: Introductionmentioning
confidence: 99%